2013
DOI: 10.1177/0003122413506440
|View full text |Cite
|
Sign up to set email alerts
|

Community Social Capital and Entrepreneurship

Abstract: The literature on social capital and entrepreneurship often explores individual benefits of social capital, such as the role of personal networks in promoting self-employment. In this article, we instead examine social capital’s public good aspects, arguing that the benefits of social trust and organization memberships accrue not just to the individual but to the community at large. We test these arguments using individual data from the 2000 Census that have been merged with two community surveys, the Social C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
148
0
18

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(171 citation statements)
references
References 99 publications
(98 reference statements)
5
148
0
18
Order By: Relevance
“…Here, we could say that, for each country in our sample, if the VOL increased by 1%, the innovative TEA increased by 0.600%, while TEA NEC decreased by 0.496%, ceteris paribus. Consistent with the reviewed literature, VOL was identified as a key factor for the innovative entrepreneurship process (Audia et al 2006;Bauernschuster et al 2010;Kwon et al 2013). As a consequence, innovation, resource mobilization and market access in regions and countries were facilitated through an enhanced associative inclination, especially in sectors of activity characterized by an innovative component (Alvarez and Busenitz 2001;Anderson et al 2007;Feldman 2014;Sorenson 2003).…”
Section: --------------------------------mentioning
confidence: 56%
See 2 more Smart Citations
“…Here, we could say that, for each country in our sample, if the VOL increased by 1%, the innovative TEA increased by 0.600%, while TEA NEC decreased by 0.496%, ceteris paribus. Consistent with the reviewed literature, VOL was identified as a key factor for the innovative entrepreneurship process (Audia et al 2006;Bauernschuster et al 2010;Kwon et al 2013). As a consequence, innovation, resource mobilization and market access in regions and countries were facilitated through an enhanced associative inclination, especially in sectors of activity characterized by an innovative component (Alvarez and Busenitz 2001;Anderson et al 2007;Feldman 2014;Sorenson 2003).…”
Section: --------------------------------mentioning
confidence: 56%
“…The extant literature has examined the impact of factors related to SPO on innovative entrepreneurial activity from different approaches, but has lacked an explicit and integrative approach. In this regard, some authors have used social capital (Anderson et al 2007;Kwon et al 2013;Leyden and Link 2015), others postmaterialist and social values (Turró et al 2014;Uhlaner and Thurik 2007), subjective well-being (Naudé et al 2013), life satisfaction , power distance (Shane 1993) and masculinity vs. femininity (Baum et al 1993).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Como lo plantea el profesor Ricardo Dávila Ladrón de Guevara: "las cooperativas locales poseen la capacidad de organizar y de acercar a los diferentes actores que se encuentran en la localidad municipal, sobre todo a la población joven ávida de desarrollar riquezas y potencialidades del municipio" (Dávila, 2004, p. 127) porque es su hábitat, es el lugar que ellos conocen y en el que siempre han vivido (Dávila, 2004, p. 128;Kwon, Heflin y Ruef, 2013).…”
Section: El Progreso De La Comunidadunclassified
“…An enormous body of research literature can be found at the individual level which, for instance, analyses how social capital improves employment situations (Franzen, Hangartner 2006, Granovetter 1995, Mouw 2003, Obukhova, Lan 2013, Thompson 2005 or related economic outcomes (Boxman et al 1991, Gerber, Mayorova 2010, Kwon et al 2013, Lancee 2010. Furthermore, Lee (2009) stated for the meso-level that "social capital is potentially an important source of competitive advantage for all organisations" (Cooke et al 2005, see Tsai, Ghoshal 1998 of these studies (Rupasingha et al 2000, Westlund, Calidoni-Lundberg 2007 analysed subnational regions in one country and the organisational density as a measure of social capital in a way that is congruent with this paper's approach (see section 3).…”
Section: Empirical Studies On Social Capital and Economic Well-beingmentioning
confidence: 99%